An acylation‐Finkelstein approach to radioiodination of bioactives: The role of amide group anchimeric assistance. (28th February 2018) - Fjellaksel, Richard; Dugalic, Damir; Demissie, Taye B.; Riss, Patrick J.; Hjelstuen, Ole‐Kristian; Sundset, Rune; Hansen, Jørn H.
Abstract: Herein, we report a straightforward sequential acylation‐Finkelstein approach to achieve iodination of amine containing bioactives. The utility was demonstrated by successful radiolabelling with 123 I in high radiochemical yield. Moreover, microwave‐assisted Finkelstein reaction can be employed to enhance conversion and reaction rates to obtain the desired iodides. The method is of interest for radioiodination of amine‐containing bioactives. The mechanistic details of the iodination process were studied by kinetics and density functional theory calculations, which revealed the mechanistic complexity of the reaction involving amide group anchimeric assistance. We disclose a number of fundamental aspects of amide group anchimeric assistance in substitution reactions. Abstract : An acylation‐Finkelstein sequence can be employed for iodination and 123‐I radioiodination of amine‐containing bioactives. Anchimeric assistance from the amide group affects the substitution rate and product outcomes. Microwave‐assisted substitution significantly enhances the conversion rates.